2017
DOI: 10.1177/2333794x17731037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Nutritional Values of Infant Formulas Available in Saudi Arabia

Abstract: Introduction. Optimum growth and development are best achieved by breastfeeding, which is the safest source for infant feeding. Mothers in Saudi Arabia start to breastfeed their infants but soon introduce formula brands. Objective. To assess the safety and nutritional adequacy of the oldest formula brands available in the Saudi market. Methods. An observational study has compared between 5 types of infant formula brands; they were chosen based on their international popularity. Also, they are considered as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Few studies have been conducted to determine the possible discrepancy between the actual and labeled nutritional contents 26 . A Saudi study compared the package labels of infant formulae with ESPGHAN Recommended Standards for the Composition of Infant Formula 27 and reported that all formulae studied were safe and nutritionally adequate. Unlike our study, their comparison was made between the information provided on the labels of the formulae's containers and ESPGHAN Recommended Standards for the Composition of Infant Formula, and no laboratory testing was involved.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been conducted to determine the possible discrepancy between the actual and labeled nutritional contents 26 . A Saudi study compared the package labels of infant formulae with ESPGHAN Recommended Standards for the Composition of Infant Formula 27 and reported that all formulae studied were safe and nutritionally adequate. Unlike our study, their comparison was made between the information provided on the labels of the formulae's containers and ESPGHAN Recommended Standards for the Composition of Infant Formula, and no laboratory testing was involved.…”
Section: Discussionmentioning
confidence: 99%